PERAN TUTOR DALAM PEMBELAJARAN DENGAN PENDEKATAN ANDRAGOGI - Waspodo, Muktiono (JIV-Jurnal Ilmiah Visi, 2009)
Most of the learners in the literacy program are adult people with various backgrounds. In teaching them the tutors should well consider the learners’ characteristics. This article discusses how to use andragogy approach in teaching the adult learners particularly in the literacy program. The difference between paedagogy and andragogy is clarified, and the role of tutor is specified in applying the andragogy approach in non formal education in general and in literacy program in particular.